A Vaccine Therapy for Canine Visceral Leishmaniasis Promoted Significant Improvement of Clinical and Immune Status with Reduction in Parasite Burden - Roatt, Bruno Mendes; Aguiar-Soares, Rodrigo Dian de Oliveira; Reis, Levi Eduardo Soares; Cardoso, Jamille Mirelle de Oliveira; Mathias, Fernando Augusto Siqueira; Brito, Rory Cristiane Fortes de; da Silva, Sydnei Magno; Gontijo, Nelder De Figueiredo; Ferreira, Sidney de Almeida; Valenzuela, Jesus G.; Corrêa-Oliveira, Rodrigo; Giunchetti, Rodolfo Cordeiro; et al. (Frontiers in Immunology, 2017)
Herein, we evaluated the treatment strategy employing a therapeutic heterologous vaccine composed of antigens of Leishmania braziliensis associated with MPL adjuvant (LBMPL vaccine) for visceral leishmaniasis (VL) in symptomatic dogs naturally infected by L. infantum. Sixteen dogs received immunotherapy with MPL adjuvant (n=6) or with a vaccine composed of antigens of L. braziliensis associated with MPL (LBMPL vaccine therapy, n=10). Dogs were submitted to an immunotherapeutic scheme consisting of 3 series composed of 10 subcutaneous doses with 10-day interval between each series. The animals were evaluated before (T0) and 90 days after treatment (T90) for their biochemical/hematological, immunological, clinical and parasitological variables. Our major results showed that the vaccine therapy with LBMPL was able to restore and normalize main biochemical (urea, AST, ALP and billirrubin) and hematological (erythrocytes, hemoglobin, hematocrit and platelets) parameters. In addition, in an ex vivo analysis using flow cytometry, dogs treated with LBMPL vaccine showed increased CD3+ T-lymphocytes and their subpopulations (TCD4+ and TCD8+), reduction of CD21+ B-lymphocytes, increased NK-cells (CD5-CD16+) and CD14+ monocytes. Under in vitro conditions, the animals developed a strong antigen-specific lymphoproliferation mainly by TCD4+ and TCD8+ cells; increasing in both TCD4+IFN-+ and TCD8+IFN-+ as well as reduction of TCD4+IL-4+ and TCD8+IL-4+ lymphocytes with an increased production of TNF- and reduced levels of IL-10. Concerning the clinical signs of CVL, the animals showed an important reduction in the number and intensity of the disease signs; increase body weight as well as reduction of splenomegaly. In addition, the LBMPL immunotherapy also promoted a reduction in parasite burden assessed by Real Time PCR. In the bone marrow, we observed seven times less parasites in LBMPL animals compared with MPL group. The skin tissue showed a reduction in parasite burden in LBMPL dogs 127.5 times higher than MPL. As expected, with skin parasite reduction promoted by immunotherapy, we observed a blocking transmission to sand flies in LBMPL dogs with only three positive dogs after xenodiagnosis. The results obtained in this study highlighted the strong potential for the use of this heterologous vaccine therapy as an important strategy for VL treatment.